PENGARUH KUALITAS PRODUK, KEPERCAYAAN DAN E-WOM TERHADAP KEPUTUSAN PEMBELIAN PRODUK SKINCARE ELFORMULA DI KOTA BATAM - Pratiwi, Dyahratna; Hikmah (LPPM Universitas Putera Batam, 2025)
This research aims to analyze the extent to which product quality, trust, and e-WOM influence the purchasing decision of Elformula Skincare products in Batam City. This study applies a quantitative approach. The sample consists of 204 respondents who are consumers who have purchased and used Elformula Skincare products in the Batu Aji and Sagulung areas, Batam City. Data were collected through primary sources. The data processing process was carried out using SPSS Version 29 software. The results of the analysis show that product quality has a positive and significant effect on the purchasing decision of Elformula Skincare in Batam City. Trust has also been shown to have a positive and significant effect on purchasing decisions. Likewise with e-WOM, which has a positive and significant impact on purchasing decisions for the product. Overall, product quality, trust, and e-WOM together have a positive and significant effect on purchasing decisions for Elformula Skincare in Batam City.